Penanganan Kasus Kecelakaan Lalu Lintas Yang Diautopsi Di Instalasi Kedokteran Forensik RSUP Dr. Sardjito Tahun 1998-2000 - I Putu Gede Dharmawan, I.B.Gd. Surya P dan Susi Hadidjah (Berita Kedokteran Masyarakat (BKM), 2004)
Background:The population booming, traffics crowd, mainly in.both air and upland, and industrial developments have been dramatically affecting disaster at great number in the worldwide. In developing countries, the traffic accident was the biggest contributor to the death under 50 years old, especially to the teen-ager. Objective: To understand frequency and distribution of traffic accident was victim's their visum et repertum records made at Forensic Medical Installation RSUP Dr. Sardjito within year of 19982000. Methods: This research based on descriptive survey, which the data is collected retrospectively from visum et repertum victim's data at Forensic Medical Installation RSUP Dr. Sardjito within year of 1998-2000. Results: The result showed that there were 283 traffic accident cases involved in .this research. Both January and November were the month with highest rank with 29 cases (10,25%).The age group of 20-29 was the highest rate with 90 cases (31,80%). Specifically, man victim is dominant with 219 cases (77,39%). Both Sleman and Bantul regency were at the highest rate with 219 cases position in traffic accident with 126 cases (44,52%) and 111 cases respectively. The victim of motorcycle accident was the highest position with 130 cases (45,93%). External examination was carried out for all victims and this research also found that there were 221 cases (2,47%) accompanied by head traumas, chest, and extremities. Conclusion: There was decrease of fatal traffics accident within 1998-2000. Keywords: traffic's accident, frequency and distribution, visum et repertum, autopsy